Cognitive functional therapy versus therapeutic exercises for the treatment of individuals with chronic shoulder pain: A protocol for a randomized controlled trial - Vander Gava; Jessica Mayara da Silva Eugenio; Ney Meziat-Filho; Lucas Araújo Almeida; Daniel Germano Maciel; Jose Diego Sales do Nascimento; Palloma Rodrigues de Andrade; Romário Nóbrega Santos Fonseca; Germanna Medeiros Barbosa; Valéria Mayaly Alves de Oliveira; Danilo Harudy Kamonseki (PLoS ONE, 2025)
Introduction Shoulder pain is a debilitating musculoskeletal condition with functional, physical, and psychological impacts. Interventions for chronic shoulder pain should address the biopsychosocial model, with Cognitive Functional Therapy (CFT) emerging as a promising physiotherapy approach. CFT approaches the multidimensional nature of pain, integrating physical and cognitive aspects. To date, no study has assessed the effectiveness of CFT in individuals with chronic shoulder pain. Therefore, this randomized controlled trial aims to compare the effects of CFT to therapeutic exercises on pain intensity, disability, self-efficacy, sleep quality, biopsychosocial aspects, and central pain processing in individuals with chronic shoulder pain. Methods This will be a randomized controlled trial, single-blinded with two parallel groups. Seventy-two individuals with chronic shoulder pain will be randomly assigned to one of two groups: CFT or Therapeutic exercise. The interventions will last 8 weeks, with the CFT group receiving therapy once a week and the therapeutic exercise group receiving sessions twice a week. The primary outcomes will be pain intensity and disability, while the secondary outcomes will include function, self-efficacy, sleep quality, biopsychosocial factors, perception of improvement/deterioration, and central pain processing. The outcome measures will be assessed at baseline, 4th week, end of treatment (8th week), and 12th-week follow-up. Conclusion The results of this study will contribute to understanding the effectiveness of CFT in treating individuals with chronic shoulder pain. Trial registration number: NCT06542666